ترجمة مقال: لـ س بينيا وخارياس: نزار قباني/ بيدرو مونتابيث الثابت في ترجمة الشعر العربي: Nizar Qabbani/ Pedro Montavez The invariant in the translation of Arabic poetry - Boukail, Amina (Maalim, 2025)
The scholars L. S. Peña and J. Arias from the University of Malaga attempt to shed light on the experience of translating Arabic poetry by Pedro Montávez, by taking his translation of Nizar Qabbani’s poems as a model for analysis and examining the most important mechanisms he uses when translating Nizar Qabbani’s poetic experience into the Spanish language. such as the metric translation, which is one of the least common mechanisms in translating poetry due to its difficulty. This article also attempts to finally answer the price that a poetry translator like Montabez might pay when translating Nizar Qabbani’s poetry into a Spanish poetic form that suits the taste of the Spanish reader.